Histomorphometric Evaluation of Allogeneic Transplantation of Bone Marrow Mesenchymal Stem Cells in Azoospermic Mice Model - Ahmad Mozafar; Davood Mehrabani; Akbar Vahdati; Ebrahim Hosseini; Mohsen Forouzanfar (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Stem cell-based therapy is one of the newest and evolving techniques in reproductive medicine. The aim of this study was to investigate the effect of allogeneic bone marrow mesenchymal stem cells (BM-MSCs) transplantation on the testis of busulfan induced azoospermia in Balb/C mice.METHODS: Eighteen adult Balb/C mice were divided into three equal groups including control, busulfan and busulfan+cell therapy (busul+CT). For induction of azoospermia, busulfan and busul+CT groups received two injections of 10 mg/Kg of busulfan intraperitoneally with 21 days interval. In the cell therapy group 35 days after the last injection of busulfan, cluster of differentiation (CD)90+/CD34-/CD45- BM-MSCs were injected into the efferent duct of testis. Eight weeks after the BM-MSCs therapy, mice were sacrificed and tissues were taken for histological and histomorphometric evaluations.RESULTS: In busul+CT group, cellular and total diameters and cellular and cross-sectional areas significantly increased in comparison to busulfan group (p˂0.001), but there were no significant differences between busul+CT and control group (p˃0.05). Numerical density and tubular count per area unit in busul+CT and control groups were significantly less than busulfan group (p˂0.001), but there were no significant difference between busul+CT and control group (p˃0.05). The luminal diameter and area showed no significant change in all groups (p˃0.05). In busul+CT group, spermatogenesis index significantly increased when compared to busulfan and control groups (p˂0.001 and p˂0.05, respectively).CONCLUSION: Histomorphometric findings showed CD90+/CD34-/CD45- BM-MSCs transplantation on the testis of busulfan-induced azoospermic in Balb/C mice recovered spermatogenesis.KEYWORDS: mesenchymal stem cell, cell therapy, azoospermia, busulfan, mouse